Comparison of Muscle Mass between Obesity Classes by Different Formulas in Diabetes Mellitus - (:unkn) unknown (SUAMTHI PUBLICATIONS, 2019)
Objective: Sarcopenia is a risk for type 2 diabetes mellitus (DM) patients, however, to diagnose sarcopenia is difficult in these patients since they are generally obese. There is more than one method used to diagnose sarcopenia. The present study aimed to compare different formulas that evaluate muscle mass among age and BMI groups in overweight and obese DM patients. Methods: The study included DM over the age of 18 years with BMI >= 25 kg/m(2). In all patients, body weight, total appendicular muscle mass (ASM), total muscle mass, and total fat mass were measured by bioimpedance method. Thereafter, skeletal muscle index was calculated dividing ASM by height (kg/m(2)); appendicular muscle mass percentage (%) was calculated dividing ASM by body weight; total muscle mass index (kg/m(2)) was calculated dividing total muscle mass by body height (kg/m(2)); and total muscle percentage (%) was calculated dividing total muscle mass by body weight. Results: Of the 486 DM patients enrolled in the study, the mean age was 54.47 +/- 8.82 years, and the mean BMI was 38.58 +/- 6.25 kg/m(2). Skeletal muscle index was 8.16 +/- 0.95 kg/m(2) in overweight, 9.23 +/- 1.04 kg/m(2) in class-1 obese, 9.95 +/- 1.05 kg/m(2) in class-2 obese, and 11.59 +/- 1.58 kg/m(2) in class-3 obese (p<0.001). Total muscle percentage was 66.18 +/- 6.63% in overweight, 58.89 +/- 5.77% in class-1 obese, 54.35 +/- 4.51% in class-2 obese, and 51.19 +/- 3.92% in class-3 obese (p<0.001). Conclusions: Total muscle percentage may be useful in assessing muscle mass in obese subjects like DM patients.
Keywords: Sarcopenia; Obesity; Skeletal muscle; Muscle weakness; Type 2 diabetes mellitus; KOREA NATIONAL-HEALTH; NUTRITION EXAMINATION; INSULIN-RESISTANCE; SARCOPENIC OBESITY; POPULATION; PREVALENCE; ADULTS